Democracy in contemporary Islamic thought and its relationship to the Shura theory - Almohamadawe, er Dr. Fadhil Abbas Jabbar (The International and Political Journal, 2023)
Since its inception, democracy has not been a type of government or a form of political system known by itself, but rather a legal or political mechanism that cannot be considered and implemented in purifying political systems from some errors, improving the performance of governments, and bringing them to a government characterized by transparency and integrity. It simply merges with most modern and contemporary political systems in order to change the political pattern or produce a new system different or developed from the old one. In Islamic political thought, the Shura theory represented an eastern synonym for Western democracy, even if it differed from it in many respects. This research seeks to clarify the similarities and differences between the two theories.